TO THE QUESTION ABOUT MEAT FREEZING. REVIEW - Andrey B. Lisitsyn; Irina M. Chernukha; Olga I. Lunina (Теория и практика переработки мяса, 2019)
The overview of studies of freezing and defrosting of raw meat, conducted during the recent years, is presented in the article. The freezing is the most effective method of preserving meat, so developments in this area are in demand by the food industry. There is noted the work on the creation of innovative technologies aimed at the optimizing of the freezing conditions (time, speed), reducing the loss of quality of the frozen products. Affected problems, which are appearing during the defrosting of meat, frozen in fresh and chilled condition. The interest of the use of the meat in the fresh state, which has not been in demand by the industry so far, is returning.